New native host plant records for frugivorous flies (Diptera: Tephritidae, Lonchaeidae) in Northeastern Brazil - Canejo, Frederico W. G.; Canejo, Rafael P. R.; Dal Molin, Anamaria; Souza, João M. A. (Entomological Communications, 2023)
The fruit flies Anastrepha fraterculus (Wiedemann, 1830), Anastrepha sororcula Zucchi, 1979, Ceratitis capitata (Wiedemann, 1824) (Diptera: Tephritidae) and Neosilba pendula (Bezzi, 1989) (Diptera: Lonchaeidae) are recorded for the first time emerging from Campomanesia dichotoma (O.Berg) Mattos and Campomanesia ilhoensis Mattos (Myrtaceae), two native species occurring in fragments of Atlantic Forest over dunes, in the northernmost limit of this biome in the state of Rio Grande do Norte, Brazil. The flies emerged from fruit samples obtained at the conservation area at Parque Estadual Dunas do Natal. The parasitoids that emerged from the puparia were also recorded, with Aganaspis pelleranoi (Brèthes) being recorded for the first time for the state. These records are of importance for monitoring and further understanding of the cycles on alternative hosts especially where these species are considered agricultural pests.